Alternatif Untuk Menjaga Kelancaran Likuiditas Dalam Perbankan Syariah - Mirwansyah Putra Ritonga (STIKes Ibnu Sina Ajibarang, 2023)
Liquidity management is a very complex problem in bank operations. The main cause of bank bankruptcy, both large and small, is not due to failure in financing which results in losses, but rather due to the inability of banks to manage liquidity. This article discusses liquidity management by utilizing the Bank Indonesia Sharia System (SBIS) and PUAS transactions. However, that the two methods have not fully resolved the actual problems faced by Islamic banking in allocating unused funds due to excess liquidity. This study was conducted through a literature search covering various solutions and alternatives to overcome the obstacles faced by Islamic banking in managing its liquidity. To support this study, secondary data was used obtained from Islamic Banking Statistics and the Financial Services Authority. Based on this study, it means that the central bank needs to develop the existing instruments in the PUAS provided by Bank Indonesia as the monetary authority. It is hoped that the liquidity problems faced by Islamic banking can be overcome more effectively.